Pemberdayaan Masyarakat Melalui Pelaksanaan Perlombaan 17 Agustus di Lingkungan Desa Sait Buttu Saribu Kecamatan Pamatang Sidamanik - ., Fatimah; Wardana, Aji; Fazura, Aghnina; Irfansyah, Ahmad; Saifurrahman, Rizky; Harahap, Nisrina Adilah; Aznura, Naya Chisa; Kataren, Yogi Karmelta (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
The 17 August activity is closely related to community empowerment activities where the 17 August activity can encourage the community to continue trying and can encourage the community to be more active and come out of the gap and be full of initiative. The aim of this activity is to increase community empowerment through holding a competition on August 17 in the Sait Buttu Saribu Pamatang Sidamanik Village environment. This research method is descriptive qualitative where the researcher tries to capture and express the meaning contained in the empirical data which is linked to secondary data in this study. The result of the empowerment process is a change in the function of the individual from being an object to a (new) subject so that existing social relations will only be characterized by relations between subjects and other subjects.